La Moselle canalisée et la voie maritime du Saint-Laurent : notes comparatives - Cermakian, Jean (Cahiers de géographie du Québec, 1967)
This paper is based upon the premise that in order to justify the considerable capital investment required in such projects, the construction of a deep-draught waterway must serve the long-term economic and political interests of the regions and nations concerned. The question then arises as to what role should such a waterway play so that those interests might be furthered. In trying to answer this question, the author suggests three hypotheses, namely that, 1. The new waterway must provide cheap transport for heavy goods of low per-unit value which can only be carried in bulk, 2. It must create or intensify exchange between two or more economic regions on the same continent, and further the international trade of those regions, and 3. It must encourage the development of under-undustrialized regions and the utilization of hitherto inaccessible natural resources.By comparing the infrastructure and the traffic of two such waterways,, one in Western Europe, the canalized Moselle river, the other one in North America, the St. Lawrence Seaway, the author attempts to verify these hypotheses empirically and finds that all three are valid in both situations. It was found that in both cases the chief result of the new waterways has been the increased competitiveness of the regions which they serve vis-à-vis more powerful neighbors in the competition for world markets.